Fatal coastal drowning incidents: A 10-year review of body recovery times in New Zealand. (December 2020) - Webber, Jonathon; Moran, Kevin; French, Claire; Fozard, Felicity; Pearless, Olivia
Highlights: The first study to report body recovery times from fatal coastal drowning incidents. Most missing persons were recovered within twenty-four hours. Most missing persons were found in the same location or close to the point of origin. Only a small proportion of missing persons were not found. Most missing persons were not wearing a lifejacket. Abstract: Despite drowning being a leading cause of unintentional injury worldwide, gaps in the data still exist. One area where limited data is available to guide lifeguards, police, search and rescue agencies, accident and forensic investigators, ocean scientists, and the coroner, is how far from the last known point (displacement) a missing person is likely to be found, and the time frame for this to occur. This lack of certainty can exacerbate the emotional toll on family, friends, and rescuers. This study aimed to describe body recovery times and displacement for fatal coastal drowning incidents in New Zealand. Using DrownBase™, the National Coronial Information System, and media reports, data were extracted for all fatal coastal-missing-person drowning incidents from 2008 to 2017. A total of 219 cases were selected. Almost all incidents involved males (92%) and minority groups (e.g., Māori and Pasifika) were over-represented. Older adults (> 42 years) were more likely to be engaged in boating, whereas for younger adults (≤ 42 years), it was swimming. Most missing persons were described as good swimmers (51%) and wearing everyday clothing (48%), yet only 4% wore a lifejacket. Most incidents were observed (63%), and rescue was attempted in 86% of cases. Most bodies (58%) were recovered within 24 h, and only 15% were not found (9%) or not reported (6%). Most missing persons (64%) were either found in the same location (57%) or <1 km from where they entered the water (7%). The quality of on-scene data limited some analysis, and the results of this study may not apply to all aquatic locations. Improved data collection could inform real-time predictive modelling of where and when a missing person might be found. The involvement of forensic and ocean scientists in future study design to widen applicability to these domains is also recommended. Fewer lives would be lost to drowning, however, if safer practices were adopted when recreating or working in, on, or around water.